Horrid Henry's monster movie - Simon, Francesca; Ross, Tony (London : Orion Children's Books, 2012)
Contains four stories that follow the adventures of Horrid Henry, including the title work in which Henry makes his very own monster movie.
Horrid Henry's monster movie -- Horrid Henry's horrid weekend -- Horrid Henry's grump card -- Horrid Henry's olympics.
"4 laugh-out-loud stories!"--Cover.
4.0
K-3.
K-3
Keywords: Horrid Henry (Fictitious character) -- Juvenile fiction; Human behavior -- Juvenile fiction; Behavior -- Fiction; Horrid Henry (Fictitious character) -- Fiction; Humorous stories; Horrid Henry (Fictional character) -- Fiction; Human behavior -- Fiction; Humorous fiction; Humorous fiction